Design, analysis, and fabrication of mechanical rice washing machine / Schufee Amani Suhaime - Schufee Amani, Suhaime (2022)
A mechanical rice washing machine is a newly developed product according to the food processing health requirements and market demand. Due to the difficulties in keeping the rice clean manually, this project aims to fabricate a mechanical rice washing machine to clean the rice and consume less energy. A mechanical rice washing machine is a machine that can speed up the process of washing rice, and it is powered by a direct current motor because it is more efficient and makes better use of its input energy. This project intends to design, analyse, and fabricate a rice washing machine that consumes less power, water, and time than washing the rice manually. In conclusion, this eco-friendly rice washing machine will benefit the lower-income family and the college student at an affordable price.